MHD Flow of a Viscous Fluid with Equal Kinematic and Magnetic Viscosity Pasta Perfectly Conducting Porous Plate - Kuiry, D. R.; Vishwakarma, D. K. (Journal of Scientific Research, 2024)
The effect of MHD flow of viscous, incompressible fluid with small electrical conductivity past an infinitely long perfectly conducting porous plate started impulsively from rest in the presence of a constant transverse magnetic field fixed relative to the fluid is investigated. We also imposed a small uniform suction or injection at the plate.Skin friction at the plate, non-dimensional forms of the velocity, and the induced magnetic field have been obtained. The graphs of velocity and magnetic field are also drawn for various values of suction, and magnetic parameters are clearly explained. From the investigations, it is found that the fluid velocity decreases due to the increasing value of kinematic viscosity and constant suction velocity. It also finds that the induced magnetic field increases due to constant suction velocity.